2017
DOI: 10.1007/s40544-017-0155-9
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous lubrication and surface microstructures of engineering polymer materials (PEEK and PI) when sliding against Si3N4

Abstract: Polyether-ether-ketone (PEEK) and polyimide (PI) are two kinds of engineering polymer materials widely used as roller bearing cages and rings under extreme environment because of their noise reduction and corrosion resistance properties. The Si 3 N 4 ceramic is the most common ball bearing material. Many current engineering applications of ball bearings require aqueous lubrication. Therefore, this study presents the aqueous lubrication of tribopairs formed by PEEK and PI material sliding against Si 3 N 4 ceram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…The influence of the different process parameters on the porous structure and mechanical properties of UHMWPE porous materials, as well as the tribological properties, was investigated in depth. This study verified the versatility of rotary sintering of a more uniform porous structure, and the tribological properties were improved, which is closer to special engineering materials such as PI and PEEK [ 36 ]. Meanwhile, it could simplify the conditions and eliminate the pre-pressing process to achieve economical and environmentally friendly effects.…”
Section: Introductionsupporting
confidence: 64%
“…The influence of the different process parameters on the porous structure and mechanical properties of UHMWPE porous materials, as well as the tribological properties, was investigated in depth. This study verified the versatility of rotary sintering of a more uniform porous structure, and the tribological properties were improved, which is closer to special engineering materials such as PI and PEEK [ 36 ]. Meanwhile, it could simplify the conditions and eliminate the pre-pressing process to achieve economical and environmentally friendly effects.…”
Section: Introductionsupporting
confidence: 64%
“…Some of the coatings associated with superlubricity have been introduced in the superlubricity section and are not covered in detail again. Here, several new advances in tribological-related coating technology are briefly introduced, such as oxide coating [183][184][185][186], metal coating [187,188], composite coating [183,185,189,190], ceramic coating [191,192], and so on.…”
Section: Lubrication Of Surface Coatingsmentioning
confidence: 99%
“…Wang et al [190] reported that the friction coefficient of carbon fiber-reinforced polyetheretherketone (CFRPEEK) is the lowest and fluctuates at approximately 0.11 and it has the lowest wear rate of 2×10 -5 mm 3 /(N•m) among the experimental materials, including CFRPEEK, carbon fiberreinforced polyamide-imide, polytetrafluoroethylene, polyoxymethylene, polyetheretherketone (PEEK), acrylonitrile butadiene styrene resin, and glass fiberepoxy resin under seawater lubrication. Wang et al [191] presented the aqueous lubrication of tribopairs formed by PEEK and PI material sliding against Si 3 N 4 ceramic. Their experimental results indicated that water as a lubricant for the PI-Si 3 N 4 tribopairs effectively reduces both friction coefficients by 35.5% and wear rates by 32% which is due to dimples appearing on the PI tribopair surfaces under water which generated additional hydrodynamic lubrication and further improved the friction properties of surface.…”
Section: Lubrication Of Surface Coatingsmentioning
confidence: 99%
“…As such, boundary lubrication might occur during braking. When operating in boundary lubrication or mixed lubrication, the hydrodynamic membrane might be a major factor that affects the friction coefficient of the samples [29][30][31][32]. It is evident from Fig.…”
Section: Friction Torque Curvementioning
confidence: 99%